2014
DOI: 10.1152/ajpendo.00511.2013
|View full text |Cite
|
Sign up to set email alerts
|

Early mitochondrial dysfunction in glycolytic muscle, but not oxidative muscle, of the fructose-fed insulin-resistant rat

Abstract: Although evidence that type 2 diabetes mellitus (T2DM) is accompanied by mitochondrial dysfunction in skeletal muscle has been accumulating, a causal link between mitochondrial dysfunction and the pathogenesis of the disease remains unclear. Our study focuses on an early stage of the disease to determine whether mitochondrial dysfunction contributes to the development of T2DM. The fructose-fed (FF) rat was used as an animal model of early T2DM. Mitochondrial respiration and acylcarnitine species were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 63 publications
2
41
0
Order By: Relevance
“…Increased long-chain carnitine esters have been observed in the serum, liver, muscle, and urine of individuals with obesity and T2D (41)(42)(43)(44)(45)(46), although reduced levels of long-chain acyl-carnitines have also been associated with metabolic syndrome and T2D ( 47 ). Rodent models of obesity and T2D also accumulate acyl-carnitines (48)(49)(50). In Drosophila , acyl-carnitines decline with age, along with obesity ( 51,52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased long-chain carnitine esters have been observed in the serum, liver, muscle, and urine of individuals with obesity and T2D (41)(42)(43)(44)(45)(46), although reduced levels of long-chain acyl-carnitines have also been associated with metabolic syndrome and T2D ( 47 ). Rodent models of obesity and T2D also accumulate acyl-carnitines (48)(49)(50). In Drosophila , acyl-carnitines decline with age, along with obesity ( 51,52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in these animal models are mostly in agreement with those obtained in human studies. The most used protocol to induce insulin resistance is overfeeding with high-fat/high-sugar diets in rats (Chanseaume et al 2006, Gomes et al 2012, Crescenzo et al 2013, Warren et al 2014 or 233:1 in mice (de Wilde et al 2008, Shelley et al 2009, Yuzefovych et al 2013, however, models of genetic obesity were also used (Holmström et al 2012). However, other observations report discrepant results, showing that high-fat feeding in rats was associated with no variation (Atgié et al 1993, De Feyter et al 2008a or even a higher mitochondrial capacity (Hancock et al 2008), and IR could be related to incomplete intramitochondrial β-oxidation (Koves et al 2008).…”
Section: Mitochondrial Dysfunction In Insulin Resistancementioning
confidence: 99%
“…2014, 2015; Warren et al. 2014). Our experience with 6‐week fructose feeding in Sprague‐Dawley rats showed that insulin‐stimulated glucose uptake was decreased in the heart without overt signs of cardiac dysfunction (Lou et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the skeletal muscle revealed fiber‐specific (glycolytic extensor digitorum longus vs. oxidative soleus) differences in their respective onset of metabolic derangements and oxidative stress, despite an overall conserved mitochondrial function and capacity (Warren et al. 2014). In this study, we aimed to characterize and elucidate the metabolic (mal)adaptations as well as oxidative stress that occur in fructose‐induced type‐2 diabetic hearts at early stages of the disease.…”
Section: Introductionmentioning
confidence: 99%